Exploring the translation of non-verbal behaviour in fiction into Malay - Haslina Haroon (Penerbit Universiti Kebangsaan Malaysia, 2022)
Non-verbal behaviour is often incorporated in literary fiction to complement or replace the verbal behaviour of characters. Because of its ability to convey messages, it is considered as equally important as verbal behaviour in a literary text. Taking this as a starting point, this study aims to explore the issue of non-verbal behaviour in translation. More specifically, the study aims to determine how the translation of non-verbal behaviour is dealt with in literary fiction, to discuss the implications of the use of different techniques in translating non-verbal behaviour, and finally to suggest techniques that can successfully convey the meaning of nonverbal behaviour in translation. The study uses as its source of data an English novel entitled A Thousand Splendid Suns, and its Malay translation, Seribu Matahari Syurga, and is guided by Poyatos’ (2002b) framework on how non-verbal behaviour can be communicated in fiction. The analysis shows that non-verbal behaviour is either described or omitted in translation. The description of non-verbal behaviour, however, does not guarantee that meaning is successfully conveyed to the target readers. Likewise, the omission of non-verbal behaviour in the translation does not automatically imply loss of meaning. What is important is the reproduction of the same function or meaning in the translated text. The findings of this study underline the importance of properly addressing non-verbal behaviour in translation and demonstrate how the functional approach in translation can be employed to find not only suitable solutions to translations problems but also those which are meaningful to the target readers.